Transboundary environmental policy effects: Markets and emission leakages - Annegrete Bruvoll; Taran Fæhn (Statistics Norway, Research Department, 2004)
According to the Environmental Kuznets Curve (EKC) literature, several mechanisms within rich economies, including increased willingness to conduct abatement policies, contribute to reduce environmental problems. Unilateral environmental policies in open economies may affect other countries negatively through trade inter-linkages. A relocation of dirty production and environmental pressure to economies with laxer abatement regimes can be one of many explanations to the apparent EKCs for rich countries. Further, the economic costs of national abatement policies may to some extent be shared with foreigners, both through lower demand for imports and through market share losses for foreign competitors producing cleaner products. In this paper, we quantify the effects of endogenous carbon tax policy in a rich and open economy, Norway, by means of a CGE model. We find that the environmental benefits fall and the economic costs rise when a global rather than a national perspective is employed.
Keywords: D58; O11; Q25; Q28; Q48; 330; Climate policy; Dynamic CGE Model; Endogenous Policy; Environmental Kuznets Curve; Pollution leakage